(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study used a mixed-approaches approach, which means it used both quantitative and qualitative methods, to look at how rural women's involvement in decision-making and economic activities helped them become more powerful. We utilized a descriptive and experimental strategy to find statistical trends and learn how context affects empowerment. Purposive sampling found rural villages where women were actively involved, and stratified random sample made sure that people of all ages, education levels, marital statuses, and economic responsibilities were included. We got quantitative data from formal face-to-face questionnaires and qualitative data from focus groups and interviews with women, community leaders, and program facilitators. We utilized SPSS to do descriptive and inferential analyses, such as correlation and regression, and NVivo software to do theme analysis of qualitative data. The results showed a substantial positive relationship (r = 0.76) between feeling empowered and being involved in making decisions. Women said they were more involved in making decisions about money, health care, and their children's education. Economic participation raised monthly income from ₹2,100 to ₹5,400 and made it easier to get credit, going from 23.3% to 74.7%. Even with these improvements, problems like having to take care of the house, not being able to move around much, and stringent social rules still exist. Support from NGOs, the government, and skill development programs were all important aspects that made participation and independence much better. The study shows that structured, inclusive techniques are a good way to help rural women become more powerful.